PENGARUH MODEL PEMBELAJARAN PICTURE AND PICTURE TERHADAP HASIL BELAJAR SISWA KELAS V PADA PEMBELAJARAN IPA SD NEGERI 091607 SINAKSAK - Gloria Kristin Damanik; Asister Fernando Siagian; Nancy Angelia Purba (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
Thils study alilms to determilne the effect of Pilcture Alnd Pilcture Lealrnilng Model on Clalss V Students' Lealrnilng Outcomes iln Scilence Lealrnilng alt SD Negeril 091607 Silnalksalk. The type of resealrch used ils qualntiltaltilve resealrch wilth the Pre-Experilment Desilgn resealrch method usilng the One Group Pretest-Posttest Desilgn form. The populaltilon of thils study were 27 students. The alveralge pretest score of students ils 44 whilch ils clalssilfiled als low but alfter the Pilcture alnd Pilcture lealrnilng model ils calrriled out there ils aln ilncrealse iln student lealrnilng outcomes alround 75.7 whilch ils ilncluded iln the good caltegory. Als for thils resealrch, ilt hals conducted vallildilty, relilalbillilty, dilffilculty level, dilfferentilaltilng power tests. The results of the N-Galiln test showed the results of 0.55, where the test results were caltegorilzed als moderalte, ilndilcaltilng the ilnfluence of the use of the Pilcture alnd Pilcture lealrnilng model on the scilence lealrnilng outcomes of gralde V students of SD Negeril 091607 Silnalksalk.